Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa Dengan Menggunakan Google Classroom Di Tingkat Sekolah Menengah Atas - Iskandar, Iskandar (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2023)
The effect of the Problem Based Learning (PBL) learning model on student learning outcomes by using Google Classroom at the high school level. This study aims to determine the extent to which the effect of the Problem Based Learning (PBL) learning model on student learning outcomes by using Google Classroom at the high school level. The population in this study were 155 students in class XI IPA at SMA Negeri 2 Peusangan in the even semester of the 2021/2022 academic year. In this study, the samples taken were XI IPA 1 totaling 30 students using purposive sampling, namely selecting samples based on certain considerations. Data were analyzed using SPSS 16.0. The research results obtained tcount = 31.140. ttable obtained with df 29, sig 0.05 (1 tailed) = 1.699, because Fcount > Ftable (31.140 > 1.699) and significance <0.05 (0.000 <0.05) thus in the calculation of the hypothesis this shows that there is a difference significant difference between learning outcomes using google classroom with even semester report card scores. So it can be concluded that there is an influence of the problem-based learning model on student learning outcomes using Google Classroom at the high school level.